2019
DOI: 10.1002/adma.201900545
|View full text |Cite
|
Sign up to set email alerts
|

SupraCells: Living Mammalian Cells Protected within Functional Modular Nanoparticle‐Based Exoskeletons

Abstract: Creating a synthetic exoskeleton from abiotic materials to protect delicate mammalian cells and impart them with new functionalities could revolutionize fields like cell-based sensing and create diverse new cellular phenotypes. Herein, we introduce the concept of 'SupraCells', which are living mammalian cells encapsulated and protected within functional modular nanoparticle-based exoskeletons. Exoskeletons are generated within seconds through immediate interparticle and cell/particle complexation that abolishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(136 citation statements)
references
References 55 publications
0
134
0
2
Order By: Relevance
“…Except for MOFs, other nanoparticles such as silica and Fe 3 O 4 can similarly self‐assemble to integrate with cells ( Figure 2 ). [ 27 ]…”
Section: Basic Methods For Organism–materials Integrationmentioning
confidence: 99%
“…Except for MOFs, other nanoparticles such as silica and Fe 3 O 4 can similarly self‐assemble to integrate with cells ( Figure 2 ). [ 27 ]…”
Section: Basic Methods For Organism–materials Integrationmentioning
confidence: 99%
“…Also some emerging brand new applications of MSNs have been proposed in biomedical fields. For instance, MSNs can be applied as functional modules to construct exoskeletons of living mammalian cells, obtaining “SupraCells” with a broad range of functionalities, such as extremophile properties (e.g., resistance to osmotic stress, reactive oxygen species, pH, and UV exposure), along with abiotic properties like magnetism, conductivity, and multifluorescence [ 120 ] (Figure 7B). We believe that more and more advances will be demonstrated in the near future and bring MSNs on a pathway to clinical trials and eventual use in the clinic.…”
Section: Emerging Bioapplications Of Porous Silica‐based Materialsmentioning
confidence: 99%
“…Reproduced with permission. [ 21 ] Copyright 2019, Wiley‐VCH. d) Left: schematic representation of photoresponsive hydrogel formation for selective cell encapsulation and right: viability of Jurkat cells before and after hydrogelation in RPMI 1640 media, 5% SDS solution, and DI water.…”
Section: Dynamic Shellsmentioning
confidence: 99%
“…Very recently, a complexly designed shell‐forming system has been reported that synergistically combined the chemical characteristics of MOF and TA (Figure 3c). [ 21 ] An artificial shell of MOF nanocrystals (MOF‐NCs), such as ZIF‐8, MIL‐100, MET‐3‐Fe, or UiO‐66‐NH 2 , was successfully formed on a living HeLa cell. Similarly to the working mechanism for Fe(III)‐TA‐MOC, the galloyl group of TA could strongly bind with the metal ion of nanocrystals, [ 22 ] and the TA linking of MOF‐NCs prevented the internalization of the nanocrystals into the cells.…”
Section: Dynamic Shellsmentioning
confidence: 99%